(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Pentoxifylline is nonspecic phospho- diesterase inhibitor used for treatment of peripheral vascular disease. This drug has some antiproteinuric effects and delay in the loss of estimated Glomerular Filtration Rate (GFR) in Diabetic Kidney Disease. To evaluate the effects of add-on pentoxifylline for reduction of albuminuria in patients with DKD. Materials and methods: 50 Eligible participants were included having DN presented with Urinary Albumin (UA) excretion greater than 30 mg/gm and having stable renal function and randomly allocated to two groups. Each group had 25 patients. Experimental group received Pentoxifylline. Both groups received Losartan and other antihypertensive and antidiabetic medication as per need. Patient were evaluated clinically with (Blood Pressure) and biochemically with (S. creatimine, eGFR, uACR, fasting blood glucose, blood glucose 2 hrs after breakfast, HBA 1 c and urinary TNF- a level) at baseline, at 3 month and at 6th month for outcome evaluation. Results: At the end of six month, uACR and urinary TNF-a decreased in the experimental group from 664±180 mg/gm and 11.72±3.73 ng/g to 567±181 and 8.85±3.57 respectively (p=<0.001). By contrast, uACR and TNF- a level did not change in the control group. Furthermore, the reduction of uACR was strongly correlated with the decrease of TNF- a (r=0.56, p=0.01) in the experimental group, but not in the control group. eGFR was stable in experimental group during 6 months but decreased rd significantly from baseline in control group (p=0.02). Treatment effect (NNT) in terms of reduction of proteinuria by >30% of baseline within 6 months was calculated and NNT was 13. Conclusion: PTX can serve as adjuvant therapy for further reducing proteinuria which may delay the progression of DN. JCMCTA 2024 ; 35 (2) : 54-60